Research on GPS/SINS Integrated Navigation System Based on Wavelet Transform - Luo Hui-Zi; Lin Xue-Yuan; Lei Liu (2011 7th International Conference on Wireless Communications, Networking and Mobile Computing, 2011)
GPS/SINS is the main direction of integrated navigation system now for it has already considered as ideal, so it plays an important role in improving performance and precision of the integrated navigation system. This article focuses on the precision of IMU outputs, using discrete wavelet transform to de-noise the output information and completes kalman filtering with GPS, then puts these results into GPS/SINS integrated navigation system, eventually by static experiment with practical data to test and verify. Experiment results show that wavelet de-noising preprocessing can obviously improve the precision of navigation parameters and thereby improve the reliability of integrated navigation system.